2015
DOI: 10.1016/j.nmni.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

First data on Pneumocystis jirovecii colonization in patients with respiratory diseases in North Lebanon

Abstract: Pneumocystis colonization may play a role in transmission and local inflammatory response. It was explored in patients with respiratory diseases in North Lebanon. Overall prevalence reached only 5.2% (95% CI 2.13–10.47) but it was higher (17.3%) in the subpopulation of patients with chronic obstructive pulmonary disease (COPD). COPD was the only factor associated with a significantly increased risk of colonization. mtLSU genotyping revealed predominance of genotype 2, identified in five patients (71.4%), inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…In the same year at other hospitals in Indonesia (RS Persahabatan and the RSCM), 14.55% of the PjP was found in 55 patients studied. The figure is lower than the state other countries 6,7 .…”
Section: Ic-biolismentioning
confidence: 61%
“…In the same year at other hospitals in Indonesia (RS Persahabatan and the RSCM), 14.55% of the PjP was found in 55 patients studied. The figure is lower than the state other countries 6,7 .…”
Section: Ic-biolismentioning
confidence: 61%
“…A high-level prevalence of P. jirovecii colonization in immunocompetent individuals has been reported in numerous studies throughout the world [2,29]. The role of P. jirovecii colonization in certain pulmonary diseases, particularly amongst patients with COPD, has gained increasing attention [5,8,9,30]. In the present multicenter study involving 403 non-HIV patients with various pulmonary diseases, we found a high prevalence of P. jirovecii colonization and this was associated with some clinical and laboratory characteristics of patients with pulmonary diseases, supporting the involvement of P. jirovecii colonization in pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, asymptomatic P. jirovecii colonization is being increasingly identified in immunocompetent individuals [2,8]. In recent years, the role of P. jirovecii colonization in pulmonary diseases has become a popular focus, especially in those with chronic obstructive pulmonary disease (COPD) and sudden infant death syndrome [5,[8][9][10][11]. These asymptomatic PJP individuals, carrying P. jirovecii, may act as an important reservoirs of nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…jirovecii colonization in immunocompetent individuals has been reported in numerous studies throughout the world [2,29]. The role of P. jirovecii colonization in certain pulmonary diseases, particularly amongst patients with COPD, has gained increasing attention [5,8,9,30]. In the present multicenter study involving 403 non-HIV patients with various pulmonary diseases, we found a high prevalence of P. jirovecii colonization and this was associated with some clinical and laboratory characteristics of patients with pulmonary diseases, supporting the involvement of P. jirovecii colonization in pulmonary diseases.…”
Section: Association Of P Jirovecii Colonization With Clinical Charamentioning
confidence: 99%
“…jirovecii colonization is being increasingly identified in immunocompetent individuals [2,8]. In recent years, the role of P. jirovecii colonization in pulmonary diseases has become a popular focus, especially in those with chronic obstructive pulmonary disease (COPD) and sudden infant death syndrome [5,[8][9][10][11]. These asymptomatic PJP individuals, carrying P. jirovecii, may act as an important reservoirs of nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%